Coastal wetlands - Catford, Alan; New South Wales. Department of Environment and Planning ([Sydney?] : Department of Environment and Planning, 1980)
Poster featuring a photograph of wetland plants, surrounded by an orange border. Title in white lettering at the foot.
Caption title.
National Library of Australia's copy has a horizontal crease across the upper edge.
Part of the John H. Young poster collection, which comprises 338 posters about the Australian environment and heritage. The collection is organised into broad subject areas: animals; birds; flora and fungi; insects and spiders; Aboriginal culture and history; Australian history and historic buildings; human rights; science and technology; industry, trade and marketing; forests and the timber industry; pollution and conservation projects; National Parks; natural areas and habitats; travel.
Also available online
Keywords: Coastal plants -- New South Wales -- Posters; Wetland ecology -- New South Wales -- Posters; Wetland plants -- New South Wales -- Posters; Wetlands -- New South Wales -- Posters; Conservation of natural resources -- Australia -- Posters; Posters, Australian; Australia -- Posters; Australian